Plants as a possible green energy source in future: Opportunities and challenges - Singh, Ajay Kumar; Soong, Lim Way; Joshi, Jetendra; Kumar, Praveen; Lean, Chong Peng (Edelweiss Applied Science and Technology, 2025)
By embedding electrode pairs into trees and plants and employing electrochemical processes, it is possible to harvest electrical energy. This energy is environmentally friendly, autonomous, and available 24/7 regardless of weather conditions. This paper discusses the effects of various external and environmental factors on the energy harvested from plants. It also explores the challenges associated with utilizing plants as batteries. It has been observed that acid trees and succulent plants are rich sources of electrical energy. The shape, size, quality, material, placement of electrodes, and the number of electrode pairs are important factors in determining the amount of energy harvested, in addition to external and environmental influences. Furthermore, it has been noted that the electrical energy output from plants can be increased through series combinations of multiple plants. Heterogeneous series connections of different plant types produce larger energy outputs than homogeneous connections. Fresh leaves generate higher potential than damaged leaves due to increased dielectric properties. The lower electrical capacity of plants is attributed to higher impedance, which varies with frequency. Lower frequencies result in reduced current compared to higher frequencies due to reactance variations. Soil temperature and humidity are also significant factors that should be considered during energy harvesting. To optimize the energy harvested from plants for use as a future battery, all external and environmental factors must be optimized, along with increasing series connections. Electronic devices or sensors placed in remote or inaccessible areas can be powered effectively by this energy source. The main challenges in using plants as batteries include their low current output and the stability of the harvested energy.